Association of inflammatory bowel disease in first‐degree relatives with risk of colorectal cancer: A nationwide case‐control study in Sweden. Issue 11 (20th February 2023) - Wang, Kai; Olén, Ola; Emilsson, Louise; Khalili, Hamed; Halfvarson, Jonas; Song, Mingyang; Ludvigsson, Jonas F.
Abstract: This study aims to assess the association between inflammatory bowel disease (IBD) history in first‐degree relatives (FDRs) and colorectal cancer (CRC) risk. We conducted a nationwide case‐control study in Sweden among 69 659 CRC cases and 343 032 non‐CRC controls matched on age, sex, birth year and residence county. Through linkage of multi‐generation register and the nationwide ESPRESSO (Epidemiology Strengthened by histoPathology Reports in Sweden) cohort, we ascertained IBD diagnoses among parents, full siblings and offspring of the index individuals. Odds ratios (ORs) of CRC associated with IBD family history were calculated using conditional logistic regression. 2.2% of both CRC cases (1566/69659) and controls (7676/343027) had ≥1 FDR with IBD history. After adjusting for family history of CRC, we observed no increased risk of CRC in FDRs of IBD patients (OR, 0.96; 95%CI, 0.91‐1.02). The null association was consistent according to IBD subtype (Crohn's disease or ulcerative colitis), number of FDRs with IBD (1 or ≥ 2), age at first IBD diagnosis in FDRs (<18, 18‐39, 40‐59 or ≥60 years), maximum location/extent of IBD or FDR relation (parent, sibling or offspring). The null association remained for early‐onset CRC (diagnosed at age <50 years). In conclusion, IBD history in FDRs was not associated with an increased risk of CRC. Our findings suggest that extra screening for CRC may not be needed in the offspring, siblings or parents of IBD patients, and strengthen the theory that it is the actual inflammation or atypia of the colon in IBD patients that confers the increased CRC risk. Abstract : What's new? Patients with inflammatory bowel disease are at an increased risk of colorectal cancer. However, the association between family history of inflammatory bowel disease and risk of colorectal cancer remains unclear. In this nationwide case‐control study, a history of inflammatory bowel disease in first‐degree relatives was not associated with an increased risk of colorectal cancer. The null association was consistent irrespective of various characteristics of inflammatory bowel disease and colorectal cancer history. The findings suggest that extra screening for colorectal cancer may not be needed in the first‐degree relatives of patients with inflammatory bowel disease.